Early changes in estimated glomerular filtration rate post-initiation of empagliflozin in EMPEROR-Preserved - Rastogi, Tripti; Ferreira, João Pedro; Butler, Javed; Kraus, Bettina Johanna; Mattheus, Michaela; Brückmann, Martina; Filippatos, Gerasimos; Wanner, Christoph; Pocock, Stuart J.; Packer, Milton; Anker, Stefan D.; Zannad, Faiez (European journal of heart failure, 2024)
Aims Renal function (estimated glomerular filtration rate [eGFR]) changes early after the introduction of empagliflozin have not been described in heart failure with preserved ejection fraction (HFpEF). The aim of this study was to describe early eGFR changes, assess its determinants and its clinical impact on cardiovascular and renal outcomes in patients with HFpEF enrolled in EMPEROR-Preserved. Methods and results Estimated glomerular filtration rate changes (absolute and relative) from randomization to week 4 were calculated and landmark analyses performed. Initial eGFR change was available in 5836 patients (97.5% of the population). Empagliflozin induced a mean eGFR change of −3.2 ml/min/1.73 m2 versus placebo from baseline to week 4. After week 4, in the empagliflozin group, the risk of the primary outcome (composite of heart failure hospitalization or cardiovascular death), cardiovascular, all-cause mortality and sustained ≥50% eGFR decrease or end-stage renal disease (ESRD) did not differ by eGFR change levels. In contrast, in the placebo group, patients included in the tertile with most profound eGFR decrease (i.e. ≥5.1% from baseline) had a higher risk of the primary outcome (hazard ratio [HR] 1.46, 95% confidence interval [CI] 1.17-1.82), cardiovascular mortality (HR 1.38, 95% CI 1.01-1.89) and sustained ≥50% eGFR decrease or ESRD (HR 2.20, 95% CI 1.20-4.04) versus tertile with eGFR increase. Conclusion An initial relatively small eGFR decrease may be expected after empagliflozin initiation. Such small eGFR decrease was not associated with adverse cardiovascular outcomes with empagliflozin. In contrast, eGFR decrease was associated with poor cardiovascular outcomes with placebo.
Vorab veröffentlicht: 21. Januar 2024
Gesehen am 13.05.2024